Thanatos (the death drive) in Mehmet Ali Çelikel's "where no one can go" kimsenin gidemediği yere - BAKIR, CAHİT (My University, 2023)
This paper attempts to offer an analysis of Mehmet Ali Celikel’s short story titled \"Where No One can Go\" in terms of Freudian psychoanalytic concept of Thanatos (the death instinct). The death instinct, which coexists with the life instinct (Eros), argues Freud, is an intrinsic part of not just human nature but Nature in general and that the true purpose of all life is death. Suggesting a positive notion of death, Freud claims that life tends inherently towards an \"inorganic existence\" or an \"inorganic world\" as the animate endeavours to revert to the inanimate which existed long before it, as a result of which the instinct to return to the inanimate state came into being. Reminiscent of Freud’s return to the inanimate state, the narrator, in Celikel’s short story, who intuitively comprehends the relationship between life and death and experiences the transcendence of self and death, embarks on a last journey towards death which is intensely craved and gladly received in order to reunite with his parents who had been long waiting for him. The paper thus aims to make an analysis of Celikel’s short story with regard to psychoanalytic relationship between memory, the drive to repeat or re-experience and death instinct.
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Batı Dilleri ve Edebiyatları; İngiliz Dili ve Edebiyatı; Social Sciences and Humanities; Philology; Western Languages and Literatures; English Language and Literature; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; EDEBİYAT; EDEBİYAT, ALMAN, HOLLANDA, İSKANDİNAV; EDEBİYAT, İNGİLİZ ADALARI; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; LITERATURE; LITERATURE, GERMAN, DUTCH, SCANDINAVIAN; LITERATURE, BRITISH ISLES; Edebiyat ve Edebiyat Teorisi; Sosyal Bilimler ve Beşeri Bilimler; Literature and Literary Theory; Social Sciences & Humanities